Exploration of Biology Learning Based on Local Wisdom in Central Java Indonesia - Eko Retno Mulyaningrum; Rivanna Citraning Rachmawati; Yuli Kurniati Werdiningsih (Indonesian Journal of Educational Science (IJES), 2026)
This research aims to explore the form of local wisdom that can be integrated in Biology learning at the high school level and analyze the challenges and opportunities for its implementation within the management of the Biology Subject Teacher Conference (Musyawarah Guru Mata Pelajaran/MGMP) of the Senior High School of Central Java Province, Indonesia. The approach used is qualitative with exploratory methods and case studies, involving interviews, Focus Group Discussions, observations, and document analysis. The subject of the study is MGMP Biology administrators who are experienced in the development of locally-based learning. The results of the study show that local wisdom such as nyadran, ngapem traditions, herbal medicine, medicinal plant utilization, and ecosystem observation have been successfully integrated into Biology learning and have a positive impact on students' cognitive abilities, affective attitudes, and psychomotor skills. However, there are several obstacles, such as limited teaching materials, lack of teacher training, lack of collaboration with the community, and limited time and curriculum flexibility. Therefore, collaboration is needed between MGMP, schools, local governments, and universities to develop contextual teaching tools, provide teacher training, and design policies that support Biology learning based on local wisdom values to be more relevant and meaningful for students.